Does the adoption of extensible business reporting language impact the quality of financial reporting? The mediating role of the e-disclosure system - Al Frijat, Yaser Saleh (Business: Theory and Practice, 2024)
The study aimed to demonstrate the mediating role of the e-disclosure system (E-DS) in the relationship between the extensible business reporting language (XBRL) and the quality of financial reporting (FRQ), for the Jordanian companies listed at the Amman Stock Exchange (ASE). This study uses AMOS to perform structural equation modelling to analyze the data; survey data was gathered from 284 respondents working across various industries and sectors listed at the ASE; 229 usable responses were received. This study finds that XBRL is positively associated with the FRQ. Further, it is found that E-DS positively influences FRQ and plays a mediating role in the connection between XBRL and FRQ. The results of this study are expected to be of high quality regarding the preparation and presentation of financial statements by XBRL. Also, the study’s findings make original contributions to developing countries other than Jordan, which are expected to benefit.